1996
DOI: 10.3177/jnsv.42.435
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Serum Alkaline Phosphatase Isoenzymes in Fasted Rats.

Abstract: SummaryChanges of serum alkaline phosphatase (sALP) isoenzymes under fasting conditions were examined using polyacrylamide gel electro phoresis (PAGE), amino-acids (L-phenylalanine (L-Phe), L-homoargi nine (L-HArg)) inhibition and wheat germ agglutinin (WGA) treatment. The sALP of non-fasted rats was separated into three bands (S1, S2, S3) by PAGE. The molecular weight (M.W.) of S1 corresponded to that of an isoenzyme found in the ileum. By the addition of L-Phe, the staining intensity of S1 was weakened, S2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It is also found in serum [3] and several types of isoenzymes have been reported [7]. We previously reported that one of the serum isoenzymes disappeared under fasting conditions [17]. In addition, this particular isoenzyme was identified as one of the isoenzymes observed in the intestine intrinsically [18].…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is also found in serum [3] and several types of isoenzymes have been reported [7]. We previously reported that one of the serum isoenzymes disappeared under fasting conditions [17]. In addition, this particular isoenzyme was identified as one of the isoenzymes observed in the intestine intrinsically [18].…”
Section: Introductionmentioning
confidence: 74%
“…): PAGE was conducted using the solution extracted from each intestinal segment [17]. After PAGE of the supernatant solution, activity staining for ALP and protein staining were conducted.…”
Section: Extraction Of Alpmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1C, the rat AP isoforms characterized by high inhibition by levamisole include the kidney and bone variants, while those present in testes, liver, and the small intestine are resistant. 8,48 tButOOH in our hands was the most consistent of all the agents assayed and thus was selected for further experimentation. tButOOH induced AP activity starting at 300 lM but the sensitivity to levamisole (percent inhibition of basal AP activity) was augmented at lower concentrations (Fig.…”
Section: Ap Increase Is Associated With Cell Toxicity and Accompaniedmentioning
confidence: 99%
“…6 Thus, the liver enzyme is more resistant to levamisole or homoarginine inhibition than either the kidney or bone isoforms. 5,7,8 The placental and intestinal enzymes have a 87%-90% similarity at the genomic level 9,10 and are generally similar in their sensitivity to chemical inhibitors, displaying only minor differences. [11][12][13][14][15] The placental isoform is reported to be the most resistant to heat as well as to inhibition by levamisole and homoarginine.…”
mentioning
confidence: 99%